Lovcenipora iranica nov. sp., an unusually large chaetetid sponge from the Upper Triassic (Howz-e Khan medmber, Nayband Formation) of northeast Iran - Senowbari-Daryan, Baba; Amirhassankhani, Fatemeh (Zitteliana, Series A, 2013)
Sponges are the most important reef builders in the bio-constructions imbedded within the Norian-Rhaetian Nayband Formation at various localities exposed in central Iran. Besides sphinctozoans and inozoans, hypercalcified sponges, i. e. chaetetids and spongiomorphids, are relatively abundant in some biohermal and biostromal reef structures. In these reefs, chaetetids are usually small (<10 cm). However, an unusually large species was found in the reefs near the village Hassan-Abad in the Ferdows area, northeast Iran. This species is described as Lovcenipora iranica nov. sp. Associated organisms are usually fragments of small-sized dendroid spongiomorphids.
UnivIS-Import:2017-11-07:Pub.2013.nat.dgeo.IGM.LP.lovcen
Keywords: Lovcenipora; chaetetid sponge; Triassic; Nayband Formation; Iran